2021
DOI: 10.1093/jn/nxab009
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Malnutrition Is Common in Patients with Coronavirus Disease 2019 (COVID-19) in Wuhan, China: A Cross-sectional Study

Abstract: Background The coronavirus disease 2019 (COVID-19) has quickly spread across the world. However, the nutritional status of COVID-19 patients has not yet been extensively examined. Objectives The aim of this study was to evaluate the nutritional status of COVID-19 patients and to identify factors independently associated with malnutrition risk. Methods In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 15 publications
3
26
1
Order By: Relevance
“…Abbreviations: COPD, chronic obstructive pulmonary disease; IQR, interquartile range.a According to the criteria of the American Thoracic Society and Infectious Diseases Society of America[23].…”
mentioning
confidence: 99%
“…Abbreviations: COPD, chronic obstructive pulmonary disease; IQR, interquartile range.a According to the criteria of the American Thoracic Society and Infectious Diseases Society of America[23].…”
mentioning
confidence: 99%
“…In a cross-sectional study that evaluates the risk of malnutrition in COVID-19 patients, no significant difference was found in the symptoms such as cough, fatigue, dyspnea, muscle soreness, headache, and diarrhea between the groups separated according to nutrition risk, although fever was more frequently observed in the patients with a higher risk of malnutrition [ 16 ]. In this study, the symptom of fever was low among the patients (18.4%) but was associated with malnutrition risk.…”
Section: Discussionmentioning
confidence: 99%
“…Using comprehensive search strategies, we identified 3,221 studies. After title and abstract screening and excluding There were three more studies that used NRS-2002 in hospitalized patients who were not in ICU [9,12,17]. Liu A, et al found lower BMI in those with a higher NRS-2002 score (p = 0.029).…”
Section: Study Characteristicsmentioning
confidence: 99%